PENJATUHAN SANKSI PIDANA TERHADAP PELAKU TINDAK PIDANA DUMPING LIMBAH B3 (STUDI PUTUSAN NOMOR 164/PID.SUS/PN SDA): Imposition Of Criminal Sanctions On Perpetrators Of Hazardous Waste (B3) Dumping Crimes (Case Study Of Decision Number 164/Pid.Sus/Pn Sda) - Muhammad Renaldy Lapaso; Maria Silvya Elisabeth Wangga (Faculty of Law, Universitas Trisakti, 2025)
Environmental damage has become a global issue with widespread impacts, one of which is caused by the illegal disposal of hazardous and toxic (B3) waste. Strict regulations are necessary to enforce sanctions against perpetrators of B3 waste dumping. However, in practice, there are cases where the enforcement of sanctions does not align with the Environmental Protection and Management Law (UU PPLH), as seen in Decision Number 164/PID.SUS/2023/PN SDA. This study examines the provisions of criminal sanctions for B3 waste dumping offenders under Article 104 of the UU PPLH and the fulfillment of special conditions in probationary sentences. Using a normative legal method with a descriptive approach, the findings result and the conclusion indicate that the imposed sanctions were not proportional to the environmental damage caused. According to B3 expert Muhammad Atjemain, such actions have the potential to cause severe and long-term environmental harm. Furthermore, the court did not impose the special conditions required for probation under Article 14c of the Indonesian Penal Code (KUHP), including the obligation to compensate for environmental damage.